Os determinantes econômicos do suicídio: Um estudo para o Brasil - Paulo R. A. Loureiro; Mario J. C. de Mendonça; Adolfo Sachsida (Instituto de Pesquisa Econômica Aplicada (IPEA), 2010)
– This article verifies the effect of economic variables over the suicide rate between Brazilian states in the period 1981-2006. The econometric results points out the importance of economic variables to explain suicide rate: income, age and poverty have negative impact over suicide, while income inequality and unemployment have positive effects over it. Furthermore, the effect of both income and unemployment over suicide is stronger in the younger segment of the population.
Keywords: I10; I12; C23; 330